2017
DOI: 10.3389/fpsyg.2016.02051
|View full text |Cite
|
Sign up to set email alerts
|

Affinity for Poetry and Aesthetic Appreciation of Joyful and Sad Poems

Abstract: Artworks with sad and affectively negative content have repeatedly been reported to elicit positive aesthetic appreciation. This topic has received much attention both in the history of poetics and aesthetics as well as in recent studies on sad films and sad music. However, poetry and aesthetic evaluations of joyful and sad poetry have received only little attention in empirical studies to date. We collected beauty and liking ratings for 24 sad and 24 joyful poems from 128 participants. Following previous stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…This is in line with other studies that have found that beauty and liking are highly correlated [ 188 , 189 ]. Nevertheless, it should be noted that beauty is by no means a prerequisite for liking [ 190 , 191 ], that is, stimuli can be liked although they are not beautiful. The close connection between beauty and liking in our data may also be related to our use of the German term schön , which means beautiful but is also used to indicate feelings of liking or pleasure.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with other studies that have found that beauty and liking are highly correlated [ 188 , 189 ]. Nevertheless, it should be noted that beauty is by no means a prerequisite for liking [ 190 , 191 ], that is, stimuli can be liked although they are not beautiful. The close connection between beauty and liking in our data may also be related to our use of the German term schön , which means beautiful but is also used to indicate feelings of liking or pleasure.…”
Section: Discussionmentioning
confidence: 99%
“…After the last session, participants should have reported less willingness to do any rereading, in being weary and less motivated. The question, "I like this poem, " was used to evaluate participants' appreciation of it (Lüdtke et al, 2014;Kraxenberger and Menninghaus, 2017). For both questions, readers indicated their agreement with the statements on a 5-point rating scale ranging from 1 = totally disagree to 5 = totally agree.…”
Section: Discussionmentioning
confidence: 99%
“…Next, participants were randomized into one of two groups: (a) the experimental group, which read the poem; or (b) the control group, which read the cooker description. Participants were instructed to silently read the poem twice, in a calm and attentive manner ( Kraxenberger and Menninghaus, 2016 ). After reading the text, participants answered two questions; one regarding understanding the content (“ I understand the meaning of the text”) and the other an affective estimation of the text (“ In my opinion, the text is pleasant ”).…”
Section: Studymentioning
confidence: 99%